Strontium enhances proliferation and osteogenic behavior of periodontal ligament cells in vitro. (12th September 2018) - Bizelli‐Silveira, Carolina; Pullisaar, Helen; Abildtrup, Lisbeth A.; Andersen, Ole Z.; Spin‐Neto, Rubens; Foss, Morten; Kraft, David C. E.
Abstract : Background and Objective: Strontium (Sr) enhances osteogenic differentiation of certain multipotent cells. Periodontal ligament cells (PDLCs) are known to be multipotent, and Sr might be useful in periodontal bone tissue engineering. This study investigates the effect of high concentration of Sr on the proliferation and osteogenic behavior of PDLCs in vitro. Material and Methods: Primary human PDLCs were cultured in MEM + 10% FBS without (Ctrl) or with Sr in four diverse concentrations: Sr1, 11.3 × 10 −3  mg/L, human serum physiological level; Sr2, 13 mg/L, typical human serum level after strontium ranelate treatment; Sr3, 130 mg/L, and Sr4, 360 mg/L. The spreading area (2, 4, 6, 24 hours), proliferation rate (1, 3, 7 days), osteogenic behavior (alkaline phosphatase ‐ ALP activity, 7 and 14 days; expression of osteogenic genes, ALP, Runt‐related transcription factor 2 ‐ RUNX2, osteopontin ‐ OPN, osteocalcin ‐ OCN, and osteoprotegerin ‐OPG, 1, 3, 7, 14, 21 days), and formation of mineralized nodules (14 and 21 days) of the PDLCs were assessed. Data were compared group‐ and period‐wise using ANOVA tests. Results: Periodontal ligament cells cultured with Sr4 showed increased spreading area (after 4 hours), proliferation rate (from 3 days), and OCN and OPN (from 7 days) gene expression as compared to Ctrl, Sr1, Sr2, and Sr3. Sr4 also led to lower ALP activity (from 7 days), ALP (from 3 days), and RUNX2 (at 7 and 14 days) gene expression, together with more evident formation of mineralized nodules, compared to Ctrl, Sr1, Sr2, and Sr3. Conclusion: Periodontal ligament cells responded to Sr4 with increased cellular proliferation and osteogenic behavior in vitro.